Hydraulic model of the skin friction reduction with surface grooves - Frohnapfel, Bettina; Jovanovic, Jovan; Lammers, Peter; Delgado, Antonio (Springer, 2008)
The reduction of skin friction in turbulent flows holds considerable promise for energy savings. The present work shows how and why skin friction and the dissipation are interrelated in turbulent channel flows. A hydraulic model formulation is presented for the skin friction reduction that can be obtained with a surface structure recently proposed for flow control. The model predictions are validated with results from direct numerical simulations. © 2008 Springer.
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.hydrau
Keywords: Flow control; Skin friction reduction; Surface structures